Park’s benefits to surrounding communities and its impact on wildlife conservation in Kainji Lake National Park, Nigeria (Journal of Biodiversity Conservation and Bioresource Management, 2023)
Projects linking conservation and development have been implemented around protected areas with a trust to generate benefits for local communities to garner support for the conservation of biodiversity in Nigeria's protected areas. Hence, this study assessed the Park's benefits to surrounding communities and its impact on wildlife conservation in Kainji Lake National Park (KLNP), Nigeria, to provide park managers with additional information in planning their activities. Four (4) randomly selected villages: Luma, Malale, Wawa and Gada Oli were surveyed with 110 questionnaire copies. The results show that the majority of respondents (55.5%) are males, whereas most households (38.18%) comprise 6 to 10 members. The major occupation of the respondents revealed that 42.7% were farmers in the surrounding national park, followed by traders (20%) and civil servants (16.4%). Most of the respondents were non-indigenes of the communities, while 37.20% of the respondents indicated that their monthly income was between ₦20,001 and ₦40,000. Eighty four per cent (84%) of the respondents agreed that the host communities' derived lots of benefits from KLNP, which include the donation of farm inputs (38.18%), employment (18.18%), empowerment programmes (16.36%) and infrastructural development (14.55%) through a majority (65%) of respondents indicated that there is no communities' involvement in the planning of park-initiated projects. The study further established that there is a significant relationship between income and the perception of respondents to wildlife conservation. However, other variables, such as age, sex, occupation, education, and household size are not significant to the notion. This study shows that Kainji Lake National Park's surrounding communities have an overall positive attitude towards the park. However, local people's responses to specific concerns and benefits showed a mixed perception. It is imperative for park authority to build on the communities' perception of conservation and development outcomes.Biodivers. Conserv. Bioresour. Manag. 2023, 9(2): 49-56